Controversies on antioxidative effects of estrogens - Stetkiewicz, Tomasz; Stachowiak, Grzegorz; Pakalski, Andrzej; Makuła, Andrzej; Surkont, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Reactive oxygen intermediates (ROI) have a role in pathological processes leadning to cell damage and concerning with etiology of many diseases. Many studies confirm antyoxidative effects of estrogens using in menopausal hormonal treatment (HT). It is still controversial issue and molecular mechanisms of this actitivity remains unclear. In this paper authors presented review of actual literature concerning with ROI and antioxidative effects of menopausal HT.